2018
DOI: 10.1080/10810730.2018.1455771
|View full text |Cite|
|
Sign up to set email alerts
|

The Effect of Vaccine Literacy on Parental Trust and Intention to Vaccinate after a Major Vaccine Scandal

Abstract: Health literacy, and more specifically vaccine literacy, might be an important factor in reducing the negative effects of exposure to misleading reports on vaccination. This study explores the association between vaccine literacy and vaccination-related outcomes after misleading reports on a scandal concerning locally produced childhood vaccines had emerged in 2016 in China. Data for this study came from a cross-sectional survey, which was conducted in April 2016 in Hangzhou, China. Data were collected in kind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 68 publications
1
50
0
Order By: Relevance
“…For instance, it may sometimes require extra time for travel health practitioners to educate patients about the safety, efficacy, and usefulness of vaccines before administration, which has implications on time convenience. Though tourism is a discretionary time and income activity, time and cost considerations could, mainly, be essential factors to tourists at the trip planning stage as they strive to plan different and complicated things ( Wang, Zhou, Leesa, & Mantwill, 2018 ). Besides vaccinations, the available time and income resources are competed for by other activities such as planning for flights and accommodation.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it may sometimes require extra time for travel health practitioners to educate patients about the safety, efficacy, and usefulness of vaccines before administration, which has implications on time convenience. Though tourism is a discretionary time and income activity, time and cost considerations could, mainly, be essential factors to tourists at the trip planning stage as they strive to plan different and complicated things ( Wang, Zhou, Leesa, & Mantwill, 2018 ). Besides vaccinations, the available time and income resources are competed for by other activities such as planning for flights and accommodation.…”
Section: Discussionmentioning
confidence: 99%
“…By using this measure, we are able to draw conclusions about the effects of HL on our dependent variables rather than self-reported HL specific to the context of early-childhood vaccination. For reasons of comparability with other studies that may apply context-specific HL measures (e.g., Aharon et al, 2017;Wang et al, 2018), we also tested our hypotheses using the self-reported functional, communicative, and critical HL scales as predictors. The results obtained with the functional HL scale are comparable with the results presented below (using the NVS).…”
Section: Discussionmentioning
confidence: 99%
“…It is still unclear whether this finding is the result of confirmation bias and only applies to parents who hold negative beliefs about early-childhood vaccination. Another study in the same context showed that people with higher HL are in fact more willing to vaccinate their children (Wang, Zhou, Lin, & Mantwill, 2018).…”
mentioning
confidence: 92%
“…The questionnaire was developed based on previous studies on risk communication, 17 , 27 , 28 and focus groups specific to understanding risk perceptions and communication related to the COVID-19 pandemic in China. Two online focus groups, each with six people in the fields of public health and medicine, were conducted to rank the most common misinformation during the epidemic.…”
Section: Methodsmentioning
confidence: 99%